PENGARUH EARNING PER SHARE DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PADA PT HERO SUPERMARKET TBK PERIODE 2012-2023 - Zakia Zulfa; Iman Lubis (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of Earning Per Share (EPS) and Price to Book Value (PBV) on the stock price of PT. Hero Supermarket, Tbk during the 2012–2023 period. A quantitative approach using multiple linier regression was employed. The partial test results show that EPS has a positive and significant effect on stock price, with a significance value of 0.039 (< 0.05) and a t-value of 2.413 (> t-table 2.262). PBV also has a positive and significant effect, with a significance value of 0.015 (< 0.05) and a t-value of 2.993 (> t-table 2.262). Simultaneously, EPS and PBV significantly affect stock prices, indicated by a significance value of 0.012 (< 0.05) and an F-value of 7.593 (> F-table 4.10). The model explains 62.8% of the variation in stock price (Adjusted R² = 0.628). These findings reinforce the fundamental theory that financial performance and market valuation together play a critical role in determining stock prices, particularly in the retail sector.